Sometimes I lie [compact disc, unabridged] - Feeney, Alice (Macmillan Audio, 2018)
Amber Reynolds knows three things for certain: she's in a coma; her husband doesn't love her anymore; and that she's told lies, but only because she thought them to be the truth.